A theory-based multi-disciplinary behavioural intervention to promote physical activity and healthy eating in overweight and obese adolescents - Fenner, Ashley Adair (Curtin University, 2014)
The current study integrated self-determination theory and goal setting theory in a multi-disciplinary family-based intervention for overweight and obese adolescents. Instructors and parents were trained in need-supportive behaviours and both adolescents and parents learned goal setting methods. Outcomes were assessed over a one-year period following an intensive 8-week intervention. Findings indicated positive changes in adolescent and parent outcomes, although no indirect pathways in the proposed mediation models were supported and changes were not sustained long-term.